1‐D reconfigurable graphene‐strips leaky‐wave antenna with different feeders for wide scanning angles. Issue 7 (10th April 2021) - Malhat, Hend A.; Elhenawy, Abdelkarim S.; Zainud‐Deen, Saber H.; El‐Shalaby, Noha A.
Abstract: This paper introduces electronic‐beam switching graphene‐strips leaky‐wave antenna (GS‐LWA) for THz wireless communications with different feeding structures. The antenna is constructed from graphene‐strips printed on silicon oxide substrate with total dimensions of 1350 × 300 × 35 μm 3 . The graphene tunable conductivity is used to control the GSLWA radiated beam direction without changing its physical structure. A scanning range of 94° (from −68° to 26°) is achieved at 2 THz using different codes. The effect of different plane wave launchers on the radiation characteristics of GS‐LWA is investigated. A planar substrate integrated waveguide horn antenna as a plane wave launcher is designed. It introduces a peak gain of 18.2 dBi with a bandwidth of 21.95% and SLL of 10.6 dB. End‐fire radiation from parabolic reflector is employed to launch plane‐wave in the GS‐LWA. A matching BW of 0.82 THz is achieved with peak gain of 18 dBi. A coplanar fed Yagi‐Uda like structure element is studied using a single element and two elements array. The two elements array provided the highest matching of −40 dB over BW of 6% and gain of 16.5 dBi. Finally, tapered microstrip line is investigated. It introduced the lowest SLL −16.1 dB with a gain of 17.5 dBi and BW of 39.57% (from 1.5 to 2.24 THz). The selection of proper feeding structure depends on the required matching BW, peak radiated gain, and the lowest SLL. Full‐wave analysis of the GS‐LWA launched by different feeding methods is introduced.